2019
DOI: 10.1503/cjs.003217
|View full text |Cite
|
Sign up to set email alerts
|

Decisional conflict in surgical patients: Should surgeons care?

Abstract: Background:The choice of surgical approach for total hip arthroplasty (THA) remains a contentious issue with regards to clinical outcome optimization and restoring patient function. The purpose of this study was to determine the impact of surgical approach for THA on quantitative gait analysis. Methods:Patients undergoing THA for primary osteoarthritis of the hip were assigned to 1 of 3 surgical approaches: anterior, posterior and lateral. Standardized implants were used at the time of surgery. Three-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Gait analysis laboratories have been used in recent studies to evaluate the effect of surgical approach on gait patterns. The anterior approach is shown to have improved early rotation range of motion (ROM) 52 and pelvic tilt closer to normal 53 compared to the posterior, but no clinically significant differences seem to emerge. 36,54 Similarly, comparison of the anterior and lateral/anterolateral approaches in postoperative gait patterns show that the anterior approach has some advantages in terms of velocity, 55,56 and closer to normal gait parameters.…”
Section: Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gait analysis laboratories have been used in recent studies to evaluate the effect of surgical approach on gait patterns. The anterior approach is shown to have improved early rotation range of motion (ROM) 52 and pelvic tilt closer to normal 53 compared to the posterior, but no clinically significant differences seem to emerge. 36,54 Similarly, comparison of the anterior and lateral/anterolateral approaches in postoperative gait patterns show that the anterior approach has some advantages in terms of velocity, 55,56 and closer to normal gait parameters.…”
Section: Advantagesmentioning
confidence: 99%
“…36,54 Similarly, comparison of the anterior and lateral/anterolateral approaches in postoperative gait patterns show that the anterior approach has some advantages in terms of velocity, 55,56 and closer to normal gait parameters. 53,57,58 The ultimate clinical effect of gait pattern alteration remains unclear, as well as the optimal way to evaluate the effect of surgical approach on muscle tissue.…”
Section: Advantagesmentioning
confidence: 99%
“…Advocates of the DAA suggested that the DAA is an intermuscular and internervous approach with less muscle and soft-tissue dissection [8]. Conversely, surgeons who favor the LA cite advantages of extensile exposure with low rates of postoperative instability [9]. Several randomized controlled trials (RCTs) have compared the DAA to the lateral approach for THA.…”
Section: Introductionmentioning
confidence: 99%
“…Stephen Petis et al (2017) abordou as três abordagens (Anterior, Lateral e Posterior) num estudo prospectivo analisando 30 pacientes submetidos a ATQ. Para o autor a escolha da abordagem cirúrgica da ATQ continua sendo uma questão controversa à respeito da otimização de resultados clínicos.…”
Section: Resultsunclassified
“…O trabalho concluiu que diferenças cinemáticas na marcha existem entre as abordagens e são estatisticamente significativas; no entanto, a relevância clínica desses achados é limitada devido a literatura estabelecida. (PETIS, 2017) Os resultados obtidos estão relacionados a heterogeneidade dos estudos, em que muitos deles contém comparações diferentes entre si e entre as abordagens, e com métodos distintos. Assim como muitos estudos deste tema relatam resultados duvidosos, devido ao pequeno número da amostra e tempo de seguimento aleatório.…”
Section: Resultsunclassified